Factors Associated with the Health-Related Quality of Life of Malaysian Young Adults Post-Pandemic - Ke Xin Lee; Kia Fatt Quek; Amutha Ramadas (MDPI AG, 2024)
The transition from school to university brings significant adjustments in lifestyle, body weight, and living environment for young adults, potentially impacting their quality of life. Emerging evidence suggests the coronavirus disease of 2019 (COVID-19) pandemic may have exacerbated these changes. This cross-sectional study involved 361 young adults (18-25 years) from Malaysian tertiary institutions, aiming to identify factors associated with health-related quality of life (HRQOL) post-COVID-19 restrictions. Data were collected online between April and July 2022, utilizing the WHOQOL-BREF for HRQOL assessment. Participants, with a median age of 23, scored highest in the physical health domain (mean: 63.2, SD = 16.2) and lowest in psychological health (mean: 58.2, SD = 16.9). Physical health domain scores varied by ethnicity, the field of study, weight category, and prescription medicine usage; environmental health scores by ethnicity and household income; and social health scores by age. Moderate perceived stress and low perceived support were significant predictors of poor HRQOL. Across the weight categories, sleep quality, perceived stress, and support have consistently impacted the HRQOL domain scores. This study underscores the multifaceted influences on young adults' quality of life during the transition to university, especially in post-pandemic adjustments, highlighting the importance of addressing factors such as perceived stress and support to enhance overall well-being.